A comparative study of prophylactic nebulized dexamethasone versus intravenous dexamethasone for prevention of postoperative sore throat in prone-position surgeries - Sarayu Ramamurthy; Guruprasad Bettaswamy (MRIMS Journal of Health Sciences)
Background: Whenever endotracheal intubation is carried out during surgeries, patients commonly complain of sore throat after surgery. For its prevention, dexamethasone has been studied and found useful. However, there are limited data on comparing the efficacy of different routes of prophylactic dexamethasone for sore throat postoperatively after lumbar spine surgery in the prone position. Objective: The objective of the study was to compare the efficacy of nebulized dexamethasone with intravenous dexamethasone for the prevention of postoperative sore throat after lumbar spine surgery in the prone position. Materials and Methods: Hospital based randomized comparative study carried out among 70 patients of the American Society of Anesthesiologists (ASA) 1 and 2 aged between 20 and 60 years. They were randomly allocated into one of the two groups. Group N received 8 mg dexamethasone in 2 ml of normal saline as nebulization 30 min before induction. Group I received 8 mg dexamethasone intravenously 5 min before induction. Postoperatively, looked for symptoms of sore throat and hoarseness of voice at 2, 6, 12, and 24 h. Results: Both groups were comparable for age, sex, ASA grades, Mallampati grades, duration of surgery, and size of the endotracheal tube. At 2, 6, 12, and 24 h after surgery, the incidence of sore throat was higher in Group I compared to Group N. These differences at each time interval were statistically significant (P < 0.05). At 6 h, the incidence in Group I patients was 65.7% compared to Group N patients (42.9%) (P < 0.05). At 12 and 24 h, the incidence of sore throat in Group I patients (60% and 37.1%, respectively) compared to Group N patients (28.6% and 17.1%, respectively) (P < 0.05). Conclusion: Eight milligram of dexamethasone in 2 ml of normal saline as nebulization 30 min before induction was found to be more effective in reducing the incidence of sore throat compared to 8 mg dexamethasone intravenously 5 min before induction.